(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses competency-based curriculum and educational unit level curriculum. The study aimed to describe the comparison between two curriculums in Islamic religious education subjects at the Madrasah Aliyah level by focusing the studies on: (a) curriculum objectives (b) curriculum material or content, (c) curriculum implementation methods, (d) curriculum evaluation, (e) similarities and differences in the objectives, content, process of implementing and evaluating of Competency-Based Curriculum and Educational Unit Level Curriculum in Islamic Religious Education. The method used in this study was a descriptive-comparative method. The approach used in this study was qualitative approach. The results of the analysis showed that 1) The purpose of the Islamic religious education curriculum is the competency-based learning Aliyah Madrasah is to develop the potential of students to face their role in the future by developing a number of life skills , while Educational unit Level I curriculum at Madrasah Aliyah is by learning expected to generate humans who seek their faith and piety to Allah, and are active in building civilization and harmony of life, which is adapted to their respective abilities.Human individuals like this are expected to have the power of strength, solid strength, in the face of all kinds of challenges and obstacles and changes that arise among the people both locally, nationally and globally 2) Material or content of competency-based curriculum of Islamic religious education at Madrasah Aliyah though schools are given the authority to compile syllabi, but still there is still intervention from central government. While the purpose of the Educational Unit Level for Islamic religious education at Madrasah Aliyah is fully given the authority to arrange the subject matter of the subject that is tailored to the needs and characteristics of the educational unit. 3) Method / learning process of Islamic religious education using competency-based level curriculum , the learning process is not only done inside but outside the classroom by participative method , and contextual approaches, using multi methods. 4) Evaluation of Competency-based curriculum and Educational Unit Level curriculum for Islamic Religious Education at Madrasahs n based on class, which emphasizes learning processes and outcomes. 5) The similarity of the Islamic religious education curriculum based on competency with the unit level education curriculum is seen in the use of learning methods and processes of learning. While the differences can be seen in curriculum objectives and formulation and the amount of subject matter.